Rekonstruksi Sejarah Hukum Pengasuhan Anak di Indonesia sebagai Dasar Penguatan Perlindungan Anak Pekerja Migran Indonesia - Maizidah Salas; Soediro Soediro (Universitas Muhammadiyah Mataram, 2026)
The rise in migration among Indonesian migrant workers (PMI) has sparked complex issues regarding the care of “left-behind children,” while conventional family law regulations have not yet been able to address the challenges of transnational child care. Therefore, a reconstruction of child care law is necessary to ensure protection that is oriented toward the best interests of the child. This normative legal study employs a legislative approach and a descriptive-qualitative analysis of the literature. The research reveals an evolution in child custody law from a parent-centered approach toward a child-centered one, although a gap still exists between regulations governing migrant labor and child protection. The results of this study indicate that legal reform can be achieved through laws that adopt several concepts or principles, such as 1) shared parenting, which involves joint child-rearing utilizing digital technology so that parenting is not constrained by time or space; 2) the application of the principles of Maqashid al-Syari’ah and Mubâdalah, so that child-rearing is fundamentally the responsibility not only of the mother but also of the father, particularly when the mother is a migrant worker; 3) strengthening Village Regulations as the closest regulatory framework for the protection and care of migrant workers’ children, 4) community-based care is effective because it stems from solidarity, commitment, and awareness, and 5) affirming the state’s responsibility, as protecting every citizen is a constitutional mandate, and the involvement of corporate social responsibility (CSR) is crucial because remittance benefits also flow to several related private sectors.